L’“indicazione formale” (formale Anzeige) della comprensione - Marassi, Massimo (Bollettino Filosofico, 2020)
In the first courses held at the University of Fribourg, Heidegger turns his attention to many themes and authors. Particular interest is devoted to the search for a suitable method to analyze the structure of lived experience and to develop an original pre-theoretical science. This phenomenological path culminates in an understanding of facticity that is configured as a hermeneutic of modality. Keywords: Facticity, Formal Indication, Hermeneutics, Method, Modality